The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1021/bc990053+
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Adamantyl Conjugated Peptide Nucleic Acids

Abstract: Peptide nucleic acids (PNA) (15-mers) conjugated to adamantyl acetic acid and labeled with fluorescein have been prepared, and their (liposome mediated) uptake in human cells in culture (HeLa, IMR-90 and MDA-MB-453) has been studied by confocal fluorescence microscopy. It is found that adamantyl-PNAs show greatly improved (endosomal) cellular uptake, but that this uptake is dependent on the cell line. Cellular uptake of such lipophilic PNAs is further mediated by cationic liposomes, and in some cases, the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…Although PNAs display strong binding affinity to their target sequence and have great potential as antisense agents, their biodelivery in the cell is very poor (47). The biodelivery of PNA into cells has been enhanced by cationic detergents (39) and by linking them with membrane-translocating peptides (51). To evaluate the uptake of the PNAtransportan conjugate in our system, we used a transportanconjugated 10-mer PNA tagged with a TAMRA fluorophore probe.…”
Section: Resultsmentioning
confidence: 99%
“…Although PNAs display strong binding affinity to their target sequence and have great potential as antisense agents, their biodelivery in the cell is very poor (47). The biodelivery of PNA into cells has been enhanced by cationic detergents (39) and by linking them with membrane-translocating peptides (51). To evaluate the uptake of the PNAtransportan conjugate in our system, we used a transportanconjugated 10-mer PNA tagged with a TAMRA fluorophore probe.…”
Section: Resultsmentioning
confidence: 99%
“…However, poor cellular uptake of PNA has been a major impediment in the development of this class of compounds as therapeutic agents. Various approaches have been adopted for the ef cient biodelivery of PNA into cells, including conjugation to lipophilic moieties (Ljungstrom et al, 1999;Muratovska et al, 2001), cell-speci c receptor ligands (Basu and Wickstrom, 1997;Boffa et al, 2000;Zhang et al, 2001), carrier peptides (Cutrona et al, 2000), neamine (Riguet et al, 2004), and guanidine-based PNA (Zhou et al, 2003) electrostatically bound with the polymeric core shell microsphere (Chiarantini et al, 2005) or loaded into the autologous red blood cells (Chiarantini et al, 1995;Turrini et al, 1991). We have demonstrated that polyamide nucleic acids complementary to the transactivation response (TAR) element of HIV-1 LTR inhibit HIV-1 production when transfected in HIV-1 infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…2 Combining within the same molecule the capacity of nucleic acids to hybridize to their complementary sequence and the biostability of pseudopeptides gives PNAs the properties of a powerful molecular tool. They can be designed with a variety of chemical modifications 3 or conjugated with carriers 4 and targeting agents, 5 and hold great promise in an array of applications (reviewed in ref. 2), including several with therapeutic potential such as antisense-, 6 antigene-, 7 antitumoral- 8 and antibacterial 5 agents.…”
Section: Introductionmentioning
confidence: 99%